Temperature Reduction Technologies Meet Asphalt Pavement: Green and Sustainability (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue, "Temperature Reduction Technologies Meet Asphalt Pavement: Green and Sustainability", covers various subjects related to advanced temperature reduction technologies in bituminous materials. It can help civil engineers and material scientists better identify underlying views for sustainable pavement constructions.